Alfabetização matemática: aspectos concernentes ao processo na perspectiva de publicações brasileiras - Maia, Madeline Gurgel Barreto (2013)
This research investigated aspects related to the process of Mathematical Literacy from research in Brazilian Mathematical Literacy, which are demanded by government publications from 1996 to 2012. We used a qualitative approach, gathering research in websites which addressed the process of alphabetization in Mathematics in the period mentioned. As we sought to know the process of Mathematical Literacy in these open publications, we found that the ideas of authors like Ole Skovsmose, Ubiratan D'Ambrosio, Ocsana Danyluk and Maria da Conceição Ferreira Fonseca Reis were mainly presented and discussed as theoretical references, which we compared. In the perspective of Ole Skovsmose, Mathematical Literacy goes beyond the individual acquisition of codes and the ability to calculate and use formal mathematical techniques. On the other hand, Mathematical Literacy in the view of Ubiratan D'Ambrosio is linked primarily to the reflection of cultural knowledge come from communities or social groups. Danyluk brings reading and writing of mathematical language, allied to the sense and meaning of knowledge as central to the process of Mathematical Literacy, which also includes speaking and listening. E, Fonseca presents Mother Tongue Education as linked to the domain of codes and symbols in the process of reading and writing. It brings yet another proposal which is Mathematical Literacy. In it are embedded forms of usage, goals, values, beliefs, attitudes, and roles related to numerical writing, ways of quantifying, ordering, measuring and classifying. We believe that the authors bring the mathematical contents, domain of codes and symbols, as well as reading and writing of mathematical language as fundamental aspects of the process of Mathematical Literacy. However, these aspects need to be directly linked to the learning context, be it social, cultural, political, economic, cognitive or mathematical. The ideas presented relate the processes of Alphabetization and Literacy in Mathematics and Mother Tongue. Mathematical Literacy may have restricted character in Mother Tongue Literacy when considering the domain of codes and symbols, reading, and writing as essential. However, such a proposal can be considered limited because it reduces the initial mathematical learning to certain technical fields. We understand that Mathematical Literacy goes far beyond this vision. It has features similar to Alphabetization proposals in the perspective of Literacy, when the content, an essential aspect of the process at issue is seen and worked within a context, be the latter mathematical, cultural, social, political, etc. and adequate to what is heard from the speech of children and captured from their records. In this view, it is not possible to read and write mathematical language without the context directly related to the origin of knowledge in development, bringing up the culture of children combined with historical perspectives of production of that knowledge